Statistical Signal Processing of Ultrasonic Signals in Norway Spruce Infected by Root and Butt Rot - Tonteri,Annika; Aliu,Aferdita (2011)
Root and butt rot in Norway spruce is costly for the forest industry and finding alternative noninvasive, efficient and cheap methods is thus of great interest. Detection of root and butt rot in Norway Spruce by analysis of an ultrasonic signal sent through standing trees could be a good alternative method. Data from Chirp-signals and sinus-waves, sent through both healthy and contaminated wood, has been used. The differences in the measured signals from the specimen, using both types of signals were analyzed with regard to their velocities and energy content. In addition the results from chirp measurements were used to analyze the differences in frequency content between healthy and contaminated wood.